Analysis of the Influence of the Work Environment and Rewards on Employee Performance at PT. MIFA Bersaudara Jakarta - I Made Aryata; Rudy Bodewyn Mangasa Tua; Cornelia Dumarya Manik (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The purpose of this research is to determine the influence of the work environment and rewards on employee performance at PT. Mifa Bersaudara Jakarta both partially and simultaneously. The method used is a quantitative method. The sampling technique used was a Slovin sample with a sample of 100 respondents. From the results of the research conducted, it is known that the work environment and rewards have a significant influence on employee performance, both partially and simultaneously. From the results of the multiple regression analysis, it is known that the regression function Y = 20.947+0.155X1+0.353X2 with a correlation value of 0.511 where the work environment and motivation only have an influence of 26.1% on employee performance and the rest is influenced by other factors.